PENGARUH STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN DAN FREE CASH FLOW TERHADAP KEBIJAKAN PEMBELIAN KEMBALI SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Ashla Rahmi Tamalla; Maslichah Maslichah; Muhammad Cholid Mawardi (Universitas Islam Malang, 2017)
ABSTRACTThis study examines the influence of ownership structure, size, and free cash flow on firms inIndonesia for their stock repurchase p[olicy aimed to distribute excess funds to stockholder.Ownership structure studied consist of institutional ownership. Sample of this study consist of15 comp[anies listed in the Indonesia Stock Exchange that repurchased their stock during theperiod of 2013-2015. The result showed that institutional investors and managerialownership negatively affect the stock repurchase. And the free cash flow and size havepositively affect the stock repurchase. The amount of influence ownership structure, size, andfree cash flow their sto[ck repurchase is 23,3%. While the influence of the remaining 76,7%is explained by other variables outside the regression equation.Keyword : Stock Repurchase, Ownership Structure, Institutional Investors, Manajerialownership, SIZE, and Free Cash Flow